2009
DOI: 10.1080/00365590802464817
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings in oral health during progression of chronic kidney disease to end-stage renal disease in a Swedish population

Abstract: Objective measurements showed that uraemic patients have more dental problems than healthy controls and the patients seem to develop their problems before they have progressed to dialysis. Therefore greater attention to dental problems may be warranted during the progression of uraemia to prevent deterioration of oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 26 publications
6
64
1
7
Order By: Relevance
“…Este estado sistémico presenta un síndrome frecuente; náuseas, vómito matinal, pérdida del apetito, astenia, adinamia, intolerancia a los cambios de temperatura, estado mental alterado, irritabilidad y alteraciones neuroló-gicas, otras alteraciones como cambios en la coloración de la piel y el olor a amoníaco de la respiración también son característicos (3,4). Estos pacientes con IRC, presentan signos y síntomas estomatológi-cos, que alteran el funcionamiento normal de la cavidad oral y como consecuencia se pueden presentar complicaciones infecciosas causadas por microorganismos que en condiciones normales compaginan e interactúan en el huésped (5). KHO S et al, 1999 evaluaron manifestaciones orales y cambios salivares en 82 pacientes con insuficiencia renal crónica en estado terminal bajo hemodiálisis, destacando que los síntomas comúnmente hallados fueron: olor y sabor urémico, boca seca, cambios en el gusto, los signos principales fueron petequias y equimosis, pseudoplaca en la lengua.…”
Section: Introductionunclassified
“…Este estado sistémico presenta un síndrome frecuente; náuseas, vómito matinal, pérdida del apetito, astenia, adinamia, intolerancia a los cambios de temperatura, estado mental alterado, irritabilidad y alteraciones neuroló-gicas, otras alteraciones como cambios en la coloración de la piel y el olor a amoníaco de la respiración también son característicos (3,4). Estos pacientes con IRC, presentan signos y síntomas estomatológi-cos, que alteran el funcionamiento normal de la cavidad oral y como consecuencia se pueden presentar complicaciones infecciosas causadas por microorganismos que en condiciones normales compaginan e interactúan en el huésped (5). KHO S et al, 1999 evaluaron manifestaciones orales y cambios salivares en 82 pacientes con insuficiencia renal crónica en estado terminal bajo hemodiálisis, destacando que los síntomas comúnmente hallados fueron: olor y sabor urémico, boca seca, cambios en el gusto, los signos principales fueron petequias y equimosis, pseudoplaca en la lengua.…”
Section: Introductionunclassified
“…38,39 Some authors did not find any significant differences even in comparison to general population. [39][40][41] Certainly, based mainly on clinical observations, CAPD patients are usually statistically better educated, mostly more responsible and receive a better care from the family. A better physical and manual fitness results in a better care of oral hygiene and more frequent dental visits.…”
Section: Periodontal Status Of Patients With Renal Failurementioning
confidence: 99%
“…A study published by Borawski et al, based on the Community Periodontal Index of Treatment Needs and described a higher prevalence of severe periodontitis among predialysis, CAPD and HD patients compared with healthy individuals (7) . In another study published by Thorman et al showed that predialysis and HD patients had significantly more clinical attachment loss than healthy subjects (20) . In our study, dental caries was found in 34% of patients.…”
Section: Discussionmentioning
confidence: 99%